2010
DOI: 10.1186/1471-2407-10-103
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin induces apoptosis of ovarian cancer cells and synergizes with doxorubicin: potential therapeutic relevance

Abstract: BackgroundOvarian carcinoma is a rarely curable disease, for which new treatment options are required. As agents that block HMG-CoA reductase and the mevalonate pathway, the statin family of drugs are used in the treatment of hypercholesterolemia and have been shown to trigger apoptosis in a tumor-specific manner. Recent clinical trials show that the addition of statins to traditional chemotherapeutic strategies can increase efficacy of targeting statin-sensitive tumors. Our goal was to assess statin-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 52 publications
11
116
0
Order By: Relevance
“…Martirossyan and colleagues showed that treatment of human ovarian carcinoma cells with lovastatin resulted in more intracellular doxorubicin accumulation and increased the drug efficacy (36). Remarkably, we observed that lovastatin treatment reduced the expression of the Shh target genes Ptc (Fig.…”
Section: Modulation Of Hh Signaling Affects Doxorubicin Accumulation supporting
confidence: 56%
See 1 more Smart Citation
“…Martirossyan and colleagues showed that treatment of human ovarian carcinoma cells with lovastatin resulted in more intracellular doxorubicin accumulation and increased the drug efficacy (36). Remarkably, we observed that lovastatin treatment reduced the expression of the Shh target genes Ptc (Fig.…”
Section: Modulation Of Hh Signaling Affects Doxorubicin Accumulation supporting
confidence: 56%
“…In this study, we show that the expression of the human Hh receptor Patched (hPtc) in Xenopus oocytes and in the yeast S. cerevisiae increased the efflux of doxorubicin, a chemotherapeutic agent used to treat recurrent cases of cancers (36). This doxorubicin efflux enhancement correlated with a decrease of doxorubicin accumulation in yeasts expressing hPtc, was energy-independent indicating that this effect was not because of ABC transporters, and was dependent of the proton motive force.…”
Section: Discussionmentioning
confidence: 73%
“…Several studies have demonstrated the pro-apoptotic action of statins, which could relate to the decreased expression of anti-apoptotic proteins such as Bcl-2 (Dimitroulakos et al, 2000), the activation of caspases 3, 7, 8 and 9 (Cafforio et al, 2005), induced apoptosis via the suppression of ERK1/2 and Akt activation (Yanae et al, 2011) and the reactivation JNK, which is a kinase that can act as a tumor suppressor (Meral et al, 2007). Some pre-clinical studies have also shown that statins have a capacity to induce synergistic antitumor effects associated with conventional chemotherapeutics (Gan et al, 2008;Martirosyan et al, 2010;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein (P-gp) inhibitory property of statins is useful for its combination treatment with other chemo therapeutic agents [63]. P-gp is a glycosylated membrane associated multi drug resistant protein and responsible for the decreased drug concentration in multi-drug resistant cells [64].…”
Section: Statins With Doxorubicinmentioning
confidence: 99%
“…When doxorubicin is used along with lovastatin in ovarian cancer cells, the statins sensitized the cells to doxorubicin and potentiated its anticancer activity synergistically. By blocking the drug efflux mediated by P-gp, Lovastatin increases the doxorubicin concentration inside the cells [63]. Simvastatin, atorvastatin or lovastatin inhibit the P-gp in high concentration [65,66].…”
Section: Statins With Doxorubicinmentioning
confidence: 99%